Sie sind auf Seite 1von 2

# 1.

Solutions
Section A k = 1 or 13
For α + β = 4,
1. ∆ = [−4(a − b)]2 − 4(a 2 + b 2 )(8)
k +1
= 16(a − b) 2 − 32(a 2 + b 2 ) =4
4k − 3
= 16[(a − b) 2 − 2(a 2 + b 2 )] k + 1 = 16k − 12
= 16(a 2 − 2ab + b 2 − 2a 2 − 2b 2 ) 13 = 15k
= −16(a 2 + 2ab + b 2 ) 13
k=
= −16(a + b) 2 15
<0
∴ The given quadratic equation has no real 4. (a) 2 x + 9 = 5 − 4 x
roots. 2 x + 9 = 5 − 4 x or 2 x + 9 = −(5 − 4 x)

2. α + β = −3 , αβ = −1 6 x = −4 or 2 x + 9 = −5 + 4 x
2
a + b = 4, ab = 2 x=− or 14 = 2 x
3
(aα + bβ ) + (bα + aβ ) = a (α + β ) + b(α + β )
2
= (a + b)(α + β ) x=− or x=7
3
= 4(−3) 2
∴ The solutions are x = − or 7.
= −12 3
(aα + bβ ) + (bα + aβ ) = abα 2 + a 2αβ +
b 2αβ + abβ 2 (b) Using (a), we have
= ab(α 2 + β 2 ) + 2
3x − 1 = − or 3 x − 1 = 7
αβ (a 2 + b 2 ) 3
= 2[(α + β ) 2 − 2αβ ] + No solutions or 3 x − 1 = ±7
8
(−1)[(a + b) 2 − 2ab] x = −2 or
3
= 2[(−3) 2 − 2(−1)] − 8
∴ The solutions are x = −2 or .
[4 − 2(2)]
2
3
= 22 − 12
= 10 (c) x − 4 = x2 − 2x − 8
The required quadratic equation is x − 4 = ( x + 2)( x − 4)
x 2 + 12 x + 10 = 0 .
x−4 = x+2 x−4
3. α −2 = β −2 x − 4 ( x + 2 − 1) = 0
α − 2 = β − 2 or α − 2 = −( β − 2) x − 4 = 0 or x + 2 = 1
α=β or α + β = 4 x=4 or x + 2 = ±1
For α = β , ∆ = 0 x=4 or ( x = −3 or − 1)
[−(k + 1)]2 − 4(4k − 3)(1) = 0 ∴ The solutions are x = −3, −1 or 4.
k 2 + 2k + 1 − 16k + 12 = 0
k 2 − 14k + 13 = 0
(k 2 − 1)(k − 13) = 0

1
Section B

5. (a) y = x 2 + ax + b
2 2
a a
= x 2 + ax +   −   + b
2 2
2
 a  a2 
=  x +  +  b − 
 2  4 
 a a2 
vertex =  − , b − 
 2 4 
a
h=−
2 (c) (i) From the figure,
a = − 2h 3
m=
a2 2
b− =k
4
(ii) Let the equation of C2 be
a2 5
b=k+ y = x 2 − 4 x + − n and the coordinates of
4 2
( −2 h ) 2
=k+ R and S be (r, 0) and (s, 0) respectively.
4
RS = r − s
= h2 + k
= (r − s ) 2

## (b) (i) α + β = 4 , αβ = c = (r + s ) 2 − 4rs

( β − α ) 2 = ( β + α ) 2 − 4αβ 5 
= 4 2 − 4 − n 
= 4 2 − 4c  2 
= 16 − 4c
= 6 + 4n
(ii) PQ = β − α RS = 2 PQ
16 − 4c = 6 6 + 4n = 2 6
∴ 16 − 4c = 6 6 + 4n = 24
5 9
c= n=
2 2
(iii) The curve C is
5
y = x2 − 4x +
2
 (−4) 5 (−4) 2 
=  − , − 
From (a), vertex  2 2 4 
 3
=  2, − 
 2